2014
DOI: 10.4209/aaqr.2013.05.0140
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Dibenzo-p-dioxin and Dibenzofuran (PCDD/F) Emission Behavior during Incineration of Laboratory Waste. Part 1: Emission Profiles Obtained Using Chemical Assay and Bioassay

Abstract: This study describes polychlorinated dibenzo-p-dioxin and dibenzofuran (PCDD/F) behavior during the incineration of laboratory waste, including combustible laboratory solid waste (LSW), laboratory plastic waste (LPW), and organic laboratory liquid waste (LLW). Stack flue gas (SFG), input materials, bottom ash (BTA), first quenching tower ash (FQA), secondary quenching tower ash (SQA), and baghouse ash (BHA) were sampled and analyzed using high-resolution gas chromatography/high-resolution mass spectrometry (HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…The reported dioxins concentration was ranged from 1.97 x 10 -3 to 8.93x 10 -1 ng I-TEQ/g (median: 4.52 x 10 -2 ng I-TEQ/g) (Hsieh, Chen, Zhu, Wu, & Huang, 2018), this was corroborated with other countries including Taiwan (laboratory waste: 0.02-1.86 ng I-TEQ/g), and Northeast China ( y ash from MSWI: 3.2-800.1 ng I-TEQ/g), respectively (J. Li et al, 2016;J.-L. Wu et al, 2014). However, these ndings were relatively higher than those found at AS3 in the present study.…”
Section: Pcdd/fs and Dl-pcbs In Ash Samplessupporting
confidence: 66%
See 1 more Smart Citation
“…The reported dioxins concentration was ranged from 1.97 x 10 -3 to 8.93x 10 -1 ng I-TEQ/g (median: 4.52 x 10 -2 ng I-TEQ/g) (Hsieh, Chen, Zhu, Wu, & Huang, 2018), this was corroborated with other countries including Taiwan (laboratory waste: 0.02-1.86 ng I-TEQ/g), and Northeast China ( y ash from MSWI: 3.2-800.1 ng I-TEQ/g), respectively (J. Li et al, 2016;J.-L. Wu et al, 2014). However, these ndings were relatively higher than those found at AS3 in the present study.…”
Section: Pcdd/fs and Dl-pcbs In Ash Samplessupporting
confidence: 66%
“…However, Dioxin and DL-PCBs concentration did not exceed the EU regulation limit in the remaining 58 samples (Esposito et al, 2009). Another study also found bovine milk contamination collected from 50 farms in risk areas in 2008-2014. The obtained result for dioxins and DL-PCBs ranged as 0.59-2.36 WHO-TEQ pg/g fat, 0.70-1.14 WHO-TEQ pg/g fat and 0.25-2.75 WHO-TEQ pg/g fat for buffalo, bovine and sheep milk, respectively (Serpe, Scaramuzzo, Maglio, Lambiase, & Esposito, 2015).…”
Section: Resultsmentioning
confidence: 94%
“…Open waste burning, backyard barrel burning, or biomass waste burning, when performed in a domestic environment, is another nonindustrial source of dioxins that must be considered, since its emission factors are already higher than those from modern industrial waste incinerators (Wevers et al, 2004;Wu et al, 2014). In fact, this is probably the most important nonindustrial source and one of the most difficult to determine precisely, given the variability in composition of waste and mostly uncontrolled combustion techniques (Lemieux et al, 2004;SolorzanoOchoa et al, 2012).…”
Section: Fingerprint Of Nonindustrial Sourcesmentioning
confidence: 99%
“…Apart from Monhol and Martins [26] who investigated the co-current combustion of dried human faeces with polyethylene waste, other co-combustion studies including those of the authors [6] , [28] , [29] have primarily focused on the use of 100% human faecal matter or surrogate faecal material [30] , [31] . While the co-combustion of faeces with polyethylene waste [26] appears to be viable, the household application of such a fuel blending process can have severe environmental and health implications, due to the potential emissions of persistent organic pollutants such as polybrominated dibenzo-p-dioxins and dibenzofurans (PBDD/Fs), polybrominated diphenyl ethers (PBDEs) and PCDD/Fs [27] . As such, a renewable energy source would be a more ideal blend material.…”
Section: Introductionmentioning
confidence: 99%